1996
DOI: 10.1088/0741-3335/38/11/005
|View full text |Cite
|
Sign up to set email alerts
|

Ion-beam and neutron production in a low-energy plasma focus

Abstract: Experimental results related to deuteron-beam production and its correlation with the neutron yield and hard x-ray production in a low-energy plasma focus device (30 kV, 5 kJ) are presented. After performing corrections in the ion energy spectrum (within an ion energy range from 50 keV to 1.5 MeV) for elastic and inelastic interactions of the ions with the background gas, it is found that the ion density at low ion energy is very high and plays an important role in the neutron production of this plasma focus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…4 MeV deuterons can produce tracks of similar depth to 3 MeV protons). However experiments have shown that for forward angles (*45°or less) proton energies are predominantly in the 3-4 MeV range [8], and that the number of deuterons with energies above 3.0 MeV is far fewer than the number of fusion protons [9]. In this situation, deuterons with just sufficient energy to pass through the Kapton film can be identified from the resulting bright shallow etched tracks they produce.…”
Section: Methodsmentioning
confidence: 99%
“…4 MeV deuterons can produce tracks of similar depth to 3 MeV protons). However experiments have shown that for forward angles (*45°or less) proton energies are predominantly in the 3-4 MeV range [8], and that the number of deuterons with energies above 3.0 MeV is far fewer than the number of fusion protons [9]. In this situation, deuterons with just sufficient energy to pass through the Kapton film can be identified from the resulting bright shallow etched tracks they produce.…”
Section: Methodsmentioning
confidence: 99%
“…Another intriguing opportunity is the possibility of optimizing axial beam production in a DPF for providing MeV beams Experimentally, on smaller devices with capacitor energies in the kJ regime, the measured axial ions have energies in the low hundreds of keV range [11,24,26]. On larger devices with capacitor energies in the 10-100 kJ range, such as the Livermore DPF,~10 14 ions with energies greater than 330 keV were detected for each pulse.…”
Section: As An Advanced Accelerator Technologymentioning
confidence: 99%
“…Typical ion fluences produced in the PF devices are 10 18 -10 20 ions/m 2 for 100 of ns to a few s time duration. The energy of ions varies from a few 100s of eV to MeV and the mean energy of ions is around 100 keV [11][12][13][14][15][16][17] depending on the operation and geometrical parameters of the PF devices. The accelerated ions produced in the PF devices are useful in applications [18][19][20][21][22][23][24] for material science, e.g.…”
Section: Introductionmentioning
confidence: 99%